Risk factors for cognitive impairment in amyotrophic lateral sclerosis: a systematic review and meta-analysis. Issue 7 (9th February 2021) - Yang, Tianmi; Hou, Yanbing; Li, Chunyu; Cao, Bei; Cheng, Yangfan; Wei, Qianqian; Zhang, Lingyu; Shang, Huifang
Abstract : Objective: Cognitive impairment is a common, far-reaching but imperceptible manifestation in patients with amyotrophic lateral sclerosis (ALS). We aimed to identify the risk factors for cognitive impairment in ALS. Methods: We searched PubMed and EMBASE for cross-sectional, case–control and cohort studies that reported predictors of cognitive impairment in ALS. The obtained data were meta-analysed to generate overall ORs and 95% CIs. Results: Twenty-seven eligible articles reporting on 6799 individuals were included out of 20 501 records. Nine predictors were identified: C9orf72 (OR 3.62, 95% CI 1.76 to 7.45), dysarthria (OR 2.25, 95% CI 1.20 to 4.22), family history of ALS (OR 1.76, 95% CI 1.18 to 2.61), predominant upper motor neuron (PUMN) phenotype (OR 1.73, 95% CI 1.09 to 2.73) and bulbar onset (OR 1.54, 95% CI 1.28 to 1.87) increased risk factors for cognitive impairment in ALS. ALS Functional Rating Scale-Revised scores, sex, age or education level were not significantly associated with cognitive impairment in ALS. In addition, C9orf72 (OR=5.94) and bulbar onset (OR=2.08) were strong predictors of ALS-frontotemporal dementia. Female sex conferred more susceptibility to executive cognitive impairment than male sex (OR=1.82). Conclusions: Patients with C9orf72 repeat expansion, dysarthria, family history of ALS, PUMN phenotype and bulbar onset had a high risk for cognitive impairment in ALS. These associations may contribute to understanding the heterogeneity of ALS. PROSPERO registration number: CRD42020201085.